Pengaruh Film Dilan 1990 Terhadap Minat Kunjungan Ke Kota Bandung Dalam Masa Pandemi COVID-19 Dengan Moderasi Perceived Risk - Angga Ranggana Putra; Mirza Fawwaz Maulasena (Fakultas Ekonomi Universitas Islam 45, 2021)
This study mainly discusses about tourism marketing with the purpose to investigate and determine the effect of Dilan 1990 movie on visit intention to Bandung. The aims of this study also to find out the different impact of visit intention after Dilan 1990 movie during pandemic COVID-19 with perceived risk as moderation. This type of research was exploratory research and used quantitative analysis. Data processing used SEM-PLS analysis techniques and the results of this study indicated that Dilan 1990 movie had a positive and significant effect to visit intention. However, between Dilan 1990 movie and visit intention to Bandung had no effect on perceived risk moderation